2014
DOI: 10.4111/kju.2014.55.6.385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Histopathological Variant on the Outcome of Patients Treated by Radical Cystectomy

Abstract: PurposeIt is well established that muscle-invasive urothelial carcinoma (UC) has a marked propensity for divergent differentiation, a fact that has significant diagnostic, prognostic, and therapeutic implications. This work is designed to assess the impact of different histopathologic variants of bladder cancer on morbidity and mortality in patients undergoing radical cystectomy (RC) as compared to the impact in patients with conventional UC.Materials and MethodsWe reviewed records of 201 patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the number of variants in that study was limited to 19 patients. 8 In Böyük et al’s study of 223 patients undergoing radical cystectomy, pathologic stage of disease, and presence of VH were found to be associated with lower CSS in the multivariate model. 9 In a meta-analysis of 23 studies involving 22 072 patients, VH was significantly associated with worse CSS (pooled HR 1.37, 95% CI).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the number of variants in that study was limited to 19 patients. 8 In Böyük et al’s study of 223 patients undergoing radical cystectomy, pathologic stage of disease, and presence of VH were found to be associated with lower CSS in the multivariate model. 9 In a meta-analysis of 23 studies involving 22 072 patients, VH was significantly associated with worse CSS (pooled HR 1.37, 95% CI).…”
Section: Discussionmentioning
confidence: 95%
“…There are studies showing that VH is associated with poorer survival on multivariate analysis. Nadeem et al 8 evaluated 201 patients that underwent RC and showed that age, gender distribution, T stage, and nodal status were not significant in predicting survival in multivariate analysis, but variant pathology was an independent risk factor for CSS. Variant pathology has also been shown to have a significant effect on OS in Cox regression analysis (hazard ratio (HR), 2.81; 95% confidence interval (CI), 1.32-5.97).…”
Section: Discussionmentioning
confidence: 99%